A law for scrap cars: the feasibility of its implementation in Malaysia / Adam Harith Zainun Hamzan and Anas Afandi Ahmad Apandi - Zainun Hamzan, Adam Harith; Ahmad Apandi, Anas Afandi (2008)
The implementation of a law on Scrap Cars may create new risks to the society. In Malaysia a car can be considered as essential item for a person. The aim of this research is to study the feasibility of implementing a law on Scrap Cars in Malaysia, which currently does not exist. The report will look on the conflicting interest between the industrial desire to implement the law to boast its sales and increase the effectiveness of cars manufacturing as oppose to the interest of the society as a whole. The literature review (Chapter 2) will emphasize is based on whether it is feasible to regulate a Scrap Cars Law. The legal chapter (Chapter 3) would provide an account of the Scrap Cars Law legal framework based on Singapore Certificate of Entitlement policy and comparison between Malaysia and Singapore in terms of the feasibility of implementing the Scrap Cars Law. It will focus on the area of coverage of the law, regulatory body which is recommended to regulate the law and the responsibility to scrap the old cars. On the finding chapter (Chapter 4) of the report, the field works deal with a respondent and some investigation and deductions derived from his perceptions on the matters relating to Scrap Cars Law. The central argument of this study will discuss on whether there is a need to implement a scrap cars law in Malaysia. The research will provide the feasibility of implementing a scrap cars law in Malaysia.